2022
DOI: 10.1038/s42255-022-00551-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages use apoptotic cell-derived methionine and DNMT3A during efferocytosis to promote tissue resolution

Abstract: Efferocytosis, the clearance of apoptotic cells (ACs) by macrophages, is critical for tissue resolution, with defects driving many diseases. Mechanisms of efferocytosis-mediated resolution are incompletely understood. Here, we show that AC-derived methionine regulates resolution through epigenetic repression of the ERK1/2 phosphatase Dusp4. We focus on two key efferocytosis-induced pro-resolving mediators, PGE2 and TGFβ1, and show that efferocytosis induces Ptgs2/COX2, leading to PGE2 synthesis and PGE2-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 55 publications
2
83
0
Order By: Relevance
“…As described above, Ampomah et al (2022) reported that efferocytosis induces PGE2 production through the CD36/ERK/Ptgs2/COX2 pathway and that PGE2 could further induce TGF‐β synthesis through the EP 2/4 , receptors, contributing to the regression of atherosclerosis. In addition, the protective role of PGE2 and TGF‐β in atherosclerosis has also been reported in several other studies, and the mechanisms are associated with anti‐inflammatory and proresolving properties (Tajbakhsh et al, 2018; Weinstock et al, 2021).…”
Section: Efferocytosis Triggering the Resolution Of Inflammation In C...mentioning
confidence: 90%
See 2 more Smart Citations
“…As described above, Ampomah et al (2022) reported that efferocytosis induces PGE2 production through the CD36/ERK/Ptgs2/COX2 pathway and that PGE2 could further induce TGF‐β synthesis through the EP 2/4 , receptors, contributing to the regression of atherosclerosis. In addition, the protective role of PGE2 and TGF‐β in atherosclerosis has also been reported in several other studies, and the mechanisms are associated with anti‐inflammatory and proresolving properties (Tajbakhsh et al, 2018; Weinstock et al, 2021).…”
Section: Efferocytosis Triggering the Resolution Of Inflammation In C...mentioning
confidence: 90%
“…In zebrafish, after tailfin amputation, macrophage clearance of ACs contributes to the production of PGE2, which drives neutrophil removal via the promotion of reverse migration through EP4 receptors and results in the resolution of inflammation (Loynes et al, 2018). In addition, PGE2 is a positive upstream molecule of TGF‐β, and as described above in this review, efferocytosis can mediate TGF‐β via the Ptgs2/COX2 pathway (Ampomah et al, 2022). In summary, efferocytosis has a powerful ability to metabolize AC‐debris and subsequently to produce PGE2 (showed in Figure 3c).…”
Section: Efferocytosis: a Link To The Resolution Of Inflammationmentioning
confidence: 93%
See 1 more Smart Citation
“…PPARγ has long been recognized as a potential receptor for PUFA produced eicosanoids ( 170 ). These effects of PUFAs on CD36 expression and the function of macrophages to produce inflammatory metabolites are at least partially mediated through the activation of PPARs by the bioactive eicosanoids produced from PUFAs ( 171 173 ). In fact, cyclooxygenase 2 (COX-2), one of the enzymes metabolizing PUFAs to eicosanoids is only expressed in tissue and infiltrating macrophages in the healthy liver ( 174 ).…”
Section: Macrophage Reprogramming In Steatosis Driven Hccmentioning
confidence: 99%
“…[7][8][9] If efferocytosis is efficient, this not only prevents postapoptotic necrosis, and concomitant proinflammatory triggers, but also contributes to resolution of existing inflammation. 10 In atherosclerosis, several molecular pathways explaining the observed defect in efferocytosis are already known, involving a.o. cleavage of receptors responsible for uptake of apoptotic cells, such as MFEG8 (milk-fat globulin e8), 11 MER Proto-Oncogene, Tyrosine Kinase (MerTK), 12,13 and LRP1 (low-density lipoprotein receptor related protein 1), and the dysregulation of eat-me ligands stimulating uptake, such as CD47.…”
Section: See Accompanying Article On Page 700mentioning
confidence: 99%